2013
DOI: 10.1039/c3cp50739d
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational self-consistent field calculations for spectroscopy of biological molecules: new algorithmic developments and applications

Abstract: This review describes the vibrational self-consistent field (VSCF) method and its other variants for computing anharmonic vibrational spectroscopy of biological molecules. The superiority and limitations of this algorithm are discussed with examples. The spectroscopic accuracy of the VSCF method is compared with experimental results and other available state-of-the-art algorithms for various biologically important systems. For large biological molecules with many vibrational modes, the scaling of computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 239 publications
(278 reference statements)
1
188
0
Order By: Relevance
“…This is a case where the VSCF algorithm fails to converge to a physical value, but frequencies of other modes, if physical can be retained. 38 The intensities, as can be seen, agree nicely in comparison with the experimental vibrational pattern.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This is a case where the VSCF algorithm fails to converge to a physical value, but frequencies of other modes, if physical can be retained. 38 The intensities, as can be seen, agree nicely in comparison with the experimental vibrational pattern.…”
Section: Resultssupporting
confidence: 70%
“…It is already found that this pair-wise coupling approximation leads to good accuracy in many applications. 22,23,38 To bring in effect of non-separability, the vibrational levels can be further corrected by second-order perturbation theory (VSCF-PT2). 33,38 This method is typically more accurate than the basic VSCF approximation.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…38 Partial charges and bond orders were calculated using NBO 39,40 analysis. In all calculations the internal coordinates were used.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, consistent procedures can be derived from QM computations of vibrational properties beyond the harmonic approximation. Recently, exact solutions for the treatment of few active modes to the vibrational problem for a generic system has been proposed 55 and effective schemes to compute vibrational frequencies within the second order vibrational perturbative (VPT2) [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] or vibrational self-consistent field (VSCF) based [76][77][78][79][80][81][82][83][84][85] approaches have been developed and implemented. In particular, a general VPT2 framework to compute thermodynamic properties, vibrational energies and transition intensities from the vibrational ground state to fundamentals, overtones and combination bands 66,67,[86][87][88] has been developed in our group.…”
Section: Introductionmentioning
confidence: 99%